Generalization of Some Simpson-Like Type Inequalities via Differentiable s-Convex Mappings in the Second Sense - Jaekeun Park (International Journal of Mathematics and Mathematical Sciences)
The author obtained new generalizations and refinements of some inequalities based on differentiable s-convex mappings in the second sense. Also, some applications to special means of real numbers are given.